Sejarah Perkembangan dan Peranan Televisi Berbasis Dakwah Islam - Effendy, Erwan; Hatahap, Santi; Rambe, Hafis Mutawalih (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This research is structured to find out, repeat, remember how the history, development and role of television for broadcasting Islamic da'wah, while the results of this research television is a mass media that has developed over time until now the development of television is getting faster, more sophisticated and can be used see everywhere, television has a function as a tool to help in getting information, information, knowledge, learning and even entertainment, television is used in many ways in their respective fields, one of which is in broadcasting Islamic da'wah television plays a very important role in Islamic da'wah broadcasting da'wah, studies Islam in the form of routine study films in a TV broadcast, television is a visible medium where not only the voice can be heard but the images can also be seen, with television the audience is more satisfied in receiving news, information, knowledge, studies and even entertainment by watching the picture so that it can make mas society is more effective in receiving information. Keywords : history, development, role, television